NILAI – NILAI SOSIAL DALAM PENYAJIAN MUSIK PANTING DI BANJARMASIN - Rima Suryana (JURNAL SOCIUS, 2015)
This study focused on answering the research problems: 1) How the description of Panting Music in Banjarmasin is, 2) How the development process of Panting Music in Banjarmasin is, 3) What social values are in Panting Music, and 4) What norms are contained in the social values?. This study was used a qualitative approach with a descriptive method, which was not limited to data collection and compilation, but includes the analysis and interpretation of the data meaning. This study is based on the theory that assesses the function and form of Panting Music performance in South Kalimantan. Based on the results obtained, it can be concluded that the function of the music has undergone many development. At first, Panting Music is referred to as a musical accompaniment of Bajapin art, where Panting has a function just as a supplementary part in the Bajapin. As the development of the Panting itself, it does not only serve as a dance accompaniment of Bajapin anymore, but also as the art of Panting. As one of the traditional arts that develop in the community, Panting is also as a medium to tighten the relationship between fellow citizens serves as entertainment, education, and high religious values contents.Keywords: Panting Music, description,development process, social value, social norms